1986
DOI: 10.1002/cne.902440408
|View full text |Cite
|
Sign up to set email alerts
|

The early embryogenesis of papillary (sweat duct) ridges in primate glabrous skin: The dermatotopic map of cutaneous mechanoreceptors and dermatoglyphics

Abstract: The present study documents the early innervation of the epidermis prior to the onset of differentiation of the papillary (sweat duct) ridge in glabrous digital skin of rhesus monkey embryos measuring 45, 50 and 55 mm (crown-rump) length. We observed small papillary ridges, spaced at a distance of approximately 40 microns, projecting into the dermis in the center of the distal glabrous digital pad of digits 2-5 in the 55-mm embryo. The other digital pads lacked any sign of ridge formation. A two-dimensional, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
48
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 82 publications
8
48
1
Order By: Relevance
“…Distorted presentations of the human body on the cortical areas are said to correlate with peripheral innervation density. Thus the hand and the fingers have high innervation density that is said to determine the dermatoglyphic characteristics of individual (Dell and Munger, 1986).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Distorted presentations of the human body on the cortical areas are said to correlate with peripheral innervation density. Thus the hand and the fingers have high innervation density that is said to determine the dermatoglyphic characteristics of individual (Dell and Munger, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…(ii) the brain and epidermal ridge (or papillary peaks) patterns on fingers (fingerprints) and palms (palmprints) develop at the same period from embryonic ectoderm (Hirsch and Schweighel, 1973). (iii) the hand and the fingers have high brain innervation density that is said to determine the dermatoglyphic characteristics of individual (Dell and Munger, 1986). (iv) individuals with a simian or single transverse palmar crease, Sydney crease have delayed development, learning difficulties and/or behavioural disorders (Johnson and Opitz, 1971;Bagga, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…These findings and associated indirect evidence about fetal development, e.g. regarding the role of homeobox genes in development of urogenital system and digits (as described above), the common endoderm derivatives of skin and nervous system [266], and the role of testosterone in stimulating production of epidermal and nerve growth factors [267,268], have led to the suggestion that dermatoglyphics can serve as a window into prenatal development.…”
Section: Introductionmentioning
confidence: 99%
“…They were recently reviewed by 26 the dermatoglyph can reflect the ontogeny of the afferent nervous system that occurred prior to papillary ridge development. Afferent nerve fibers provide a two-dimensional grid that could modulate the spacing and arrangement of the papillary and sweat duct ridges of successive digits 24 . Bonnevie 17 also suggested that there is a direct relationship between cutaneous nerve distribution and the location of the centers of ridge patterns.…”
Section: Discussionmentioning
confidence: 99%
“…• Classical methods of light microscopy 2,3,21 • Methods of scanning electron microscopy 22,23 • Methods of transmission electron microscopy 24 • Methods of immunohistochemistry (for identify structures of afferent nerves and Merkel cells) 25,26 212…”
Section: Introductionmentioning
confidence: 99%